1984
DOI: 10.1021/jm00377a014
|View full text |Cite
|
Sign up to set email alerts
|

Bispyridinamines: a new class of topical antimicrobial agents as inhibitors of dental plaque

Abstract: A series of N,N'-polyalkylenebis[4-(substituted-amino)pyridines] has been prepared, and members have been evaluated as potential anti-dental plaque agents. From among the most active members of the series, one compound, N,N'-[1,10-decanediyldi-1(4H)-pyridinyl-4-ylidene]bis(1-octanam ine) dihydrochloride, octenidine, was selected as a candidate for clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 2 publications
2
41
1
2
Order By: Relevance
“…In earlier studies, the MICs of OCT and CHG against a variety of test bacteria were quite similar (2,20). In this study, the bactericidal activity of OCT was superior to that of CHG, especially against Staphylococcus aureus and Streptococcus pyogenes.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…In earlier studies, the MICs of OCT and CHG against a variety of test bacteria were quite similar (2,20). In this study, the bactericidal activity of OCT was superior to that of CHG, especially against Staphylococcus aureus and Streptococcus pyogenes.…”
Section: Resultssupporting
confidence: 57%
“…Octenidine hydrochloride (OCT) ( (2). Previous studies with this compound have shown it to be effective in inhibiting the growth of plaqueforming bacteria (16,20,21) and in reducing development of plaque in both experimental animals (6,16) and humans (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its unspecific, strong absorption and interaction with cell wall and cell membrane structures, octenidine has a broad antimicrobial spectrum against Grampositive and Gram-negative bacteria including MRSA [1] [84,85] . Octenidine is superior to chlorhexidine and alexidine as an inhibitor of plaque-forming enzymes of Streptococcus mutans [84] .…”
Section: Spectrum Of Activitymentioning
confidence: 99%
“…Therefore, there is a need for an effective disinfectant that can eliminate listerial biofilms in the presence of organic matter at a wide range of temperatures. Octenidine hydrochloride (OH) is a positively charged bispyridinamine that exhibits antimicrobial activity against plaque-producing organisms, such as Streptococcus mutans and Streptococcus sanguis (5). Toxicity studies with a variety of species have shown that OH is not absorbed through mucous membranes and the gastrointestinal tract, and there have been no reports of carcinogenicity, genotoxicity, or mutagenicity of this compound (17,19,29).…”
mentioning
confidence: 99%